Penurunan Kadar Krom Pada Air Limbah Elektroplating dengan Menggunakan Bentonit Aktif Sebagai Adsorben - Mustafa Mustafa; Muh Irwan (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Chrome by product comes not only from elektroplating industry but also textile industry, leather tanning and laboratory waste. Looking at its existence and hazard, chrome by product has to further handled in order not to give negative effects to living creatures and environment. To avoid polluting the environment, the waste has to be processed first by lowering its content. One of the methods to reduce the content of the heavy metal is adsorption by using active bentonite as adsorbent. The purpose of this research is to find out the ability of active bentonite in reducting the content of chrome by product in waste. The procedure in this research consists of bentonite preparation, bentonite activation, content of chrome analysis in the raw material (waste water electroplating). The optimum treatment for the adsorption was at the mass of 25 gram stirred at 597 rpm with the contact time of 4 hours. Adsorption at the mass 25 grams could reduce chrome content from the initial chrome content waste water 394.59 mg/L to 194.34 mg/L with the reduction of chrome of 49.48%